Transplantasi Terumbu Karang Menggunakan Media Bioreeftek Di Perairan Pulau Dodola Kabupaten Pulau Morotai - Kismanto Koroy; Iswandi Wahab; Djainudin Alwi; Rinto M Nur; Nurafni Nurafni; Asy’ari Asy’ari (Journal Of Khairun Community Services, 2021)
Coral reefs and all the life in them is one of the natural wealth owned and priceless. However, based on the research results, the condition of dead coral in the waters of Dodola Island by 4% caused by the anchor of the ship. To reduce damage to coral reef ecosystems that continue to be developed today is to apply coral transplant techniques. The purpose of community service activities is to understand planting techniques and socialization of the role and function of coral reefs to tourists on the importance of coral reefs in Dodola water. The devotional activities include design, preparation of materials tools, manufacturing and harvesting of coral seeds, and installing seeds in bioreeftek media. Socialization and understanding of biographic coral reef transplant technology are carried out on the community, especially tourists. Before the activity is carried out, generally, the public does not know the importance of coral reefs and the benefits of transplantation. After socialization, the community begins to understand and understand the importance of coral reefs